Sprawozdanie z Ogólnopolskiej Konferencji Naukowej pt. „Procesy modernizacyjne w Europie Środkowo-Wschodniej w perspektywie historycznej” - SIEBIESZUK, Damian (Historia i Świat, 2017)
Overview and description of the Regional Scientific Conference "Modernization processes in Central and Eastern Europe in a historical perspective" at Siedlce University (2017.03.08)